COMPARISON OF VIRTUAL ANALYSIS OF DIOSGENIN AND TIGOGENIN WHICH HAS POTENTIAL DOWN-REGULATING ANDROGEN SIGNALING - Safitri, Erinda Hidayatus; R., Januar F.; N., Shifaaun (JSMARTech, 2019)
Costus speciosus contain several compounds that are important for fitocontraception, such as diosgenin and tigogenin. This study focused on analyzing the potential of diosgenin and tigogenin to down-regulate the androgen signaling with in silico. The androgen receptor (AR) was downloaded from the protein database with ID number 1A28. The diosgenin (CID: 119245) and tigogenin (CID: 99516) were obtained from Pubchem. Optimizing the energy of ligands was established using Pyrx. AR was docked with diosgenin and tigogenin using Hex 8.0.0. The interactions were visualized by Discovery Studio Client 3.5. The results showed that the interaction in the complex of Androgen receptor with diosgenin (ARD) and Androgen receptor with tigogenin (ART) occured in the ligand binding domain (LBD) area. ART had two hydrogen bonds (PRO817 and VAL818), while ARD had only one hydrogen bond (GLN798). There were 11 Van Der Walls bonds in ARD and 5 Van Der Walls bonds in ART. ARD still had unfavorable bump. ART had more hydrophobic bonds and alkyl groups than ARD. The energy binding of ART was also smaller than that of ARD, -264 kcal/mol compared to -249 kcal/mol. This study indicated that ART is more potential in the down-regulating mechanism of androgen signaling.